A phenomenological study of the lived experiences of social housing residents in relation to their digital exclusion - Williams, Jonathan (Graduate School of Business (GSB), 2020)
There is no more significant threat to a prosperous South Africa than the persistent socioeconomic exclusion and continuous spatial segregation of South African society. Social housing and digital inclusion both play a critical role as inclusionary interventions for the socioeconomic advancement of the previously disenfranchised and the reintegration of apartheid-era segregated communities. Access to ICTs provides marginalised communities with platforms and tools to amplify their voices, gain access to information and reaffirm their citizenship, thereby allowing for more vigorous participation in the national discourse. “The goal of ICTs is not to necessarily solve the digital divide but rather to further the process of social inclusion.” (Warschauer, 2003) Furthermore, these technological platforms provide access to life chances, capital enhancing activities, information and the possibility of building networks outside of individuals' modest social networks. This study seeks to understand how digital exclusion influences the experience of overall inclusion in South African social housing. This dissertation is a qualitative study employing a mixture of phenomenological and ethnographic methods to document and make sense of the lived experiences of participants in relation to their exclusion. The study uses of semi-structured interviews, focus groups and surveys to explore participants' adaptation and integration into local formal institutions and the host community of Blue View Terraces, a mostly white, middle-income neighbourhood located in Cape Town. The study discovered the coexistence of many different and competing forms of exclusion. Firstly, a key finding during the process of residential desegregation or spatial inclusion was participants' pervasive experiences of power dynamics. These power dynamics manifested as discrimination and marginalisation that was partly caused by the absence of relocation support, public awareness programs about social housing and a failure by the social housing institution to adequately address more forms of inclusion than just spatial. Secondly, the findings showed the design of the housing development to be hopelessly inadequate to support newcomers' actual lives. Necessary infrastructure was omitted in favour of a lower build cost. This led to a higher cost of living that is unaffordable for social housing residents and negates the benefits of lower cost rental accommodation. Lastly, findings showed that digital exclusion negatively influences the adjustment of low-socioeconomic status children into high-socioeconomic schools and leads to forced assimilation when learners come into daily contact with schools in their locality. The findings signify that social and economic inclusion efforts and even building projects can and should not be considered in isolation. Each form of exclusion competes with another, often exacerbating its effects. Also, of significance is the default approach to integration in South African schools of assimilation rather than multiculturalism. The outcomes of this study highlight the importance of considering multiple forms of exclusion together rather than in isolation, especially in the context of social inclusion projects.